Peranan Media Sosial Tiktok Dalam Menyebarkan Berita Terkini Inspira Tv - Amalia, Syfa Putri; Taufik, Reza Rizkina (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The emergence of new media, one of which is the social media TikTok, in mass communication has had a significant impact, especially on the dissemination of news information on this new media, so that many news media have taken part in using TikTok as an alternative forum for spreading their news, such as the Inspira TV news media. This research aims to show the role of TikTok as an alternative forum for disseminating news information for Inspira TV. This research uses a qualitative approach method and the study used is a case study with a constructivist research paradigm and is assisted by new media theory. Research data was collected using in-depth interviews and online observations. The results of this research are that the strategy used by Inspira TV is in the information processing process which is made straightforward and clear, as well as in the implementation process using several elements contained in the new TikTok media. The comments on the Inspira TV news account are varied, including positive, negative and zero feedback. The difference felt by the Inspira TV news media in disseminating its news is its affordability, the dissemination process, and the content of the news. So Inspira TV as a news media considers that the role of social media TikTok in disseminating the latest news. Inspira TV is still not effective enough, because it still has limitations and shortcomings in processing news..